Tumor necrosis factor- α, adiponectin and their ratio in gestational diabetes mellitus - Ali Khosrowbeygi; Mohammad Reza Rezvanfar; Hassan Ahmadvand (Babol University of Medical Sciences, 2018)
Background: It has been suggested that inflammation might be implicated in the gestational diabetes mellitus (GDM) complications, including insulin resistance. The aims of the current study were to explore maternal circulating values of TNF-α, adiponectin and the adiponectin/TNF-α ratio in women with GDM compared with normal pregnancy and their relationships with metabolic syndrome biomarkers. Methods: Forty women with GDM and 40 normal pregnant women were included in the study. Commercially available enzyme-linked immunosorbent assay methods were used to measure serum levels of TNF-α and total adiponectin. Results: Women with GDM had higher values of TNF-α (225.08±27.35 vs 115.68±12.64 pg/ml, p<0.001) and lower values of adiponectin (4.50±0.38 vs 6.37±0.59 µg/ml, P=0.003) and the adiponectin/TNF-α ratio (4.31±0.05 vs 4.80±0.07, P<0.001) than normal pregnant women. The adiponectin/TNF-α ratio showed  negative correlations with insulin resistance (r=-0.68, p<0.001) and triglyceride (r=-0.39, P=0.014) and a positive correlation with insulin sensitivity (r=0.69, p<0.001). Multiple linear regression analysis showed that values of the adiponectin /TNF-α ratio were independently associated with insulin resistance. Binary logistic regression analysis showed that GDM was negatively associated with adiponectin /TNF-α ratio. Conclusions: In summary, the adiponectin/TNF-α ratio decreased significantly in GDM compared with normal pregnancy. The ratio might be an informative biomarker for assessment of pregnant women at high risk of insulin resistance and dyslipidemia and for diagnosis and therapeutic monitoring aims in GDM